Creative problem solving skills for students of the College of Education for Pure Sciences - Abdul Hassan, Maitham Mohammed; Abbood, Suhad Abdul Ameer (مجلة الشرق الأوسط للعلوم التربوية والنفسية, 2023)
The aim of the current research is to identify the extent to which students of the College of Education for Pure Sciences / Department of Chemistry possess creative problem solving skills, and to identify the differences in their creative problem solving skills according to gender variables (males - females), and the research was determined by students of the College of Education for Pure Sciences - Ibn Al-Haytham / Department of Chemistry / the third stage, for the academic year 2020-2021, and the descriptive research method was adopted, and the size of the research sample was (372) students who were randomly selected. To achieve the objectives of the research, the researchers prepared a test for the creative solving skills of problems of the type of objective questions and essays, which in its final form consisted of (27) paragraphs, and the validity and reliability of the test were verified. The data was processed statistically, the (t-test) equation was used for one sample, the results showed that the research sample possessed creative problem solving skills, and the statistical method (t-test) was used for two independent samples to verify the existence of differences in creative problem solving skills according to gender variables. The results showed that there were no differences between the sexes. In light of the results, the researchers recommended including thinking education programs in the stages of the Chemistry Department and employing educational activities that develop creative problem solving skills for students of faculties of education. It was suggested that a study of creative problem solving skills be conducted experimentally with independent variables such as ( Generative thinking, systems thinking, systems intelligence).